IMPACT OF ROAD ALIGNMENT ON FUEL CONSUMPTION AND GAS EMISSIONS – EXPERIMENTAL AND ANALYTICAL RESEARCH (Advances in Civil and Architectural Engineering, 2023)
This research analysed the impact of road alignment on the fuel consumption and gas emissions of a vehicle driven at a free-flow speed by an 85th percentile driver. The field experiment included constant and free-flow speed rides by a personal car equipped with a high-performance (10 Hz) Bluetooth global position device and on-board diagnostics connector, with which the travel path, speed, acceleration, and consumption data were recorded. Regression analyses of the dependence of free-flow speed and fuel consumption on the geometric characteristics of the road (curvature, length, longitudinal slope, etc.) resulted in the formation of a reliable model that could compare alternative road designs for a given corridor in terms of route economy and safety. The main parameters contributing to the consumption on tangents were the slope and radii of adjacent curves. For constant speed, the slope was the only geometric parameter that had an impact on fuel consumption.